2021
DOI: 10.1111/pce.14041
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling foliar water uptake pathways: The contribution of stomata and the cuticle

Abstract: Plants can absorb water through their leaf surfaces, a phenomenon commonly referred to as foliar water uptake (FWU). Despite the physiological importance of FWU, the pathways and mechanisms underlying the process are not well known.Using a novel experimental approach, we parsed out the contribution of the stomata and the cuticle to FWU in two species with Mediterranean (Prunus dulcis) and temperate (Pyrus communis) origin. The hydraulic parameters of FWU were derived by analysing mass and water potential chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 75 publications
2
26
0
Order By: Relevance
“…where Ψ i and Ψ f are the initial and final leaf water potentials, respectively, C leaf is FWU divided by the absolute change in Ψ (Ψ f À Ψ i ) measured on individual leaves, and t is the duration leaf wetting (Binks et al, 2019;Brodribb & Holbrook, 2003;Guzm an-Delgado et al, 2021).…”
Section: Pathway Kinetics and Effect Of Season And Dehydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…where Ψ i and Ψ f are the initial and final leaf water potentials, respectively, C leaf is FWU divided by the absolute change in Ψ (Ψ f À Ψ i ) measured on individual leaves, and t is the duration leaf wetting (Binks et al, 2019;Brodribb & Holbrook, 2003;Guzm an-Delgado et al, 2021).…”
Section: Pathway Kinetics and Effect Of Season And Dehydrationmentioning
confidence: 99%
“…Though the value of intercepted atmospheric water sources may be greatest during drought (Breshears et al, 2008), differences between the effects of drought and leaf dehydration on FWU kinetics remain unclear. Numerous studies have reported increases in mass and leaf water potential (Ψ leaf ) with leaf wetting (Berry et al, 2019); however, leaf conductance to surface water (K surf ; μmol H 2 O s À1 m À2 MPa À1 ), which normalizes the flux into the leaf by the driving gradient, has been reported far less (Binks et al, 2016(Binks et al, , 2019Fuenzalida et al, 2019;Guzm an-Delgado et al, 2021;Guzm an-Delgado, Earles, & Zwieniecki, 2018). Among species and FWU pathways, differences in K surf and FWU rehydration kinetics with respect to seasonality and dehydration offer insights into how FWU might be integrated in plant-water movement frameworks in different ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf trichomes, depending on their density, composition and structure, are the major media for water absorption in a Mediterranean (Quercus ilex) and a temperate (Fagus sylvatica) species [5,6]. In addition, in two species without leaf trichomes or hydathodes, open stomata have been observed to play a major role in water uptake over cuticles when exposed to fog [7]. Leaf water absorption can also be involved in the recovery of leaf [8] and stem [9,10] hydraulic functions after drought-or frost-induced xylem embolism.…”
Section: Introductionmentioning
confidence: 99%
“…The pathway water takes when entering Sequoia leaves is still unknown; wax coverage and stomatal density most strongly increase hydraulic resistance, suggesting that water crosses the cuticle, yet larger stomatal size modestly lowers resistance, indicating that some water may enter that way (Figure 3A). In angiosperms, two-thirds of fog uptake enters leaves as vapor diffusing through stomata with the rest crossing the cuticle (Guzmán-Delgado et al, 2021); however, further work is needed to explore uptake pathways in conifers. Peripheral leaves with especially low visible wax coverage do not have uptake rates as high as axial shoots with comparable wax levels (Figure 3B), suggesting that other traits are influential.…”
Section: Discussionmentioning
confidence: 99%